(untitled) (Research, Society and Development, 2023)
Objective: To evaluate the ethnopharmacological knowledge applied to the use of medicinal plants in patients with leishmaniasis assisted in the Health Regional of the municipality of Pinheiro-MA. Methodology: This is a descriptive, cross-sectional study with data collection, the application of questionnaires was used to identify the main plants used by the participants in the treatment of leishmaniasis in the municipality of Pinheiro-MA, the data were analyzed and structured by the Software Microsoft Excel 2016. Results: A total of 26 respondents were obtained, being a study with a convenience sample, regarding the use of plants, 50% of the participants used medicinal plants, among the most mentioned plants are aloe, garlic, sunflower oil, mastruz and capeba. The plants that were most cited were selected from the study, namely: Aloe Vera, Allium Sativum L., Chenopodium ambrosioides L., Citrus sinensis, Copaifera reticulada ducke, Attalea speciosa. Conclusion: From this research it was possible to observe that the use of medicinal plants has a considerable prevalence in patients diagnosed with leishmaniasis. Plants such as Aloe Vera, Allium Sativum L., Chenopodium ambrosioides L., Citrus sinensis, Copaifera reticulada ducke, Attalea speciosa, are reported in studies available in the literature as species that present direct leishmanicidal activities. These data are essential for the development of new treatment alternatives. Therefore, a greater incentive and continuity for research on this subject is needed, taking into account the various benefits of using natural products, such as accessibility, low cost, low toxicity and proven efficiency.